1989
DOI: 10.1007/bf00036509
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of Minuartia verna and Thlaspi alpestre in the British Isles in relation to 13 soil metals

Abstract: The plant-communities from habitats of the metallophyte species Minuartia verna and Thlaspi alpestre (T. caerulescens) at sites disturbed and undisturbed by mining are described. Four communities were delineated by cluster and principal component analysis. Group 1 comprised species-poor communities on disturbed non-calcareous soils; group 2, relatively species-rich communities on disturbed calcareous soils; group 3, species-rich communities in the main on undisturbed calcareous soils. Group 4 consisted of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…1), and it name which proved to be illegitimate (Gutermann, also occurs on both undisturbed (naturally 1975) Manv other earlier names have been applied mineralized) and disturbed (mine and smelter waste) regionally to British and other European material sites. Other more detailed field studies (Shimwell, 1968; Smith, 1979;Hajar, 1987;Garcia-Gonzalez & Clark, 1989) have confirmed this preference of the species for soils of high heavy metal (zinc, cadmium and lead) status.…”
Section: Introduction ^J^^^ Clear That T Caerulescens Is a Highly Pomentioning
confidence: 73%
“…1), and it name which proved to be illegitimate (Gutermann, also occurs on both undisturbed (naturally 1975) Manv other earlier names have been applied mineralized) and disturbed (mine and smelter waste) regionally to British and other European material sites. Other more detailed field studies (Shimwell, 1968; Smith, 1979;Hajar, 1987;Garcia-Gonzalez & Clark, 1989) have confirmed this preference of the species for soils of high heavy metal (zinc, cadmium and lead) status.…”
Section: Introduction ^J^^^ Clear That T Caerulescens Is a Highly Pomentioning
confidence: 73%
“…Zn–Cd enriched) and serpentine soil (Reeves & Brooks, 1983; Lloyd‐Thomas, 1995). Its occurrence on nonmetalliferous substrates has been more recently acknowledged, possibly because such populations are extremely rare in Great Britain, where the species ecology has been most thoroughly studied (Ingrouille & Smirnoff, 1986; Garcia‐Gonzalez & Clark, 1989; Baker et al ., 1994). Nonmetallicolous populations are apparently not rare in continental Europe (Koch et al ., 1998), where they often occur in mountain grassland (Ellenberg, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Thiaspi caerulescetts J. & C. Presl (Brassicaceae) occurs mainly on Zn/Pb-enriched soils, and also on serpentines and non-mineralized soils (Ingrouille & Smirnoff 1986;Garcia-Gonzalez & Clark 1989;Baker & Proctor 1990), and has been identified as a Zn hyperaccumulator (Reeves & Brooks 1983). This speeies has attracted much interest reeently, beeause its potential to extraet large amounts of heavy metals from soils may be exploited in phytoremediation of contaminated land (McGrath et al 1993;Baker et al 1994a;Brown et al 1995a).…”
Section: Introductionmentioning
confidence: 99%